Implementation of Edunesia Learning Media Platform Based on Mobile Ionic Typescript - Putu Adi Guna Permana; Ni Luh Gede Pivin Suwirmayanti; I Gede Surya Rahayuda; Ni Luh Putu Linda Santiari (Proceeding of International Conference on Information Science and Technology Innovation (ICoSTEC), 2022)
In the era of the Internet of Things as it is today, especially in the world of education, where information can be accessed quickly, can be accessed from anywhere and anytime, it will be very helpful in the learning process and interaction between teachers and students. One method that we can apply is the existence of an application that can bridge the learning process between students and teachers, so that distance and time are no longer an obstacle, especially during this COVID-19 pandemic, such as when there is a communication PSBB between teachers and students at school. Some use Whatsapp Groups, the use of Whatsapp groups is considered less well organized, both from the material presented or the tasks given. This also supports the Industrial Revolution 4.0 where we try to prepare from an early age so that the learning process and interaction between students and teachers, apart from face-to-face, can also get used to doing distance learning. With the resources and limitations of schools, it is not an easy and cheap job to make such an application. For this reason, we dream of presenting an educational platform that can automatically initiate applications that can support today's digital learning processes or methods. Schools will be able and able to make their respective school applications easily and quickly. To answer this problem, the author tries to solve it by presenting an educational platform that can be used to create school applications independently. Edunesia platform produces applications needed for learning media or material delivery, while the applications produced by this platform include Web Admin (content manager), Teacher Android Mobile Application, and Student Android Mobile Apps. The resulting application is complete with features that support learning activities from home, such as learning videos, student and teacher consultations, Online Classrooms (Video Conference).